Evaluation Methods of Consumer Satisfaction with Infrastructure Services - AIMESHEVA, Zhannat Salavatovna (Journal of Advanced Research in Law and Economics; Vol 7 No 6 (2016): Vol 7, No 6(2016): JARLE, Volume VII, Issue 6(20), Fall 2016, 2017)
The paper deals with methodological aspects of understanding of the place of infrastructure and services rendered on its basis to customers. Infrastructure services are differentiated by measures and methods of carrying out in the Republic of Kazakhstan. Consumer preferences are analyzed based on the private and state approach to the problems range of provided services and selection of potential institutional forms is substantiated. An analysis of system operator’ service activity technical-economic indicators is carried out. Market infrastructure services are systematized, the subject matter of infrastructure services in the electric industry is revealed. The evaluation procedure for system operators’ service quality in the electric industry based on power supply reliability and stability indicators is developed. Calculations of mathematical and statistical characteristics of customers’ partial estimates (given scores) as random values with the normal probability law (density function) are made.
Keywords: type of economic activity; infrastructure services; service systematization; service quality evaluation; efficient management; consumer satisfaction